THE FORMATION AND DISSIPATION OF A METEOR COMA - Kramer, E. N.; Shestaka, I. S. (Одеські астрономічні публікації, 2017)
The results of reduction of instantaneous fireball photographs are presented. The observational data testify to the fact that linear dimensions of the region radiating after the meteor’s flight amount to tens and hundreds of meters, and in the case of particularly bright fireballs to some kilometers. The suggested by authors hypothesis of synchronous length change of the region of fireball afterglow alongside with its light variation is verified. The analysis of the spectral photograph obtained by authors with the method of instantaneous exposure shows that the afterglow proceeds mainly to radiation in H and K lines of Call. Several mechanisms of ionized atoms afterglow of the meteor substance are discussed. Photometric profiles of the instantaneous images of meteors are compared with theoretical calculations made both on the supposition of the parent body fragmentation and on that of afterglow of ionized atoms of meteor substance. The conclusion on a joint effect of both above-mentioned mechanisms is obtained